An integrated approach for the valorization of mango seed kernel: Efficient extraction solvent selection, phytochemical profiling and antiproliferative activity assessment (2019)
A novel valorization strategy is proposed in this work for the sustainable utilization of a major mango processing waste (i.e. mango seed kernel, MSK), integrating green pressurized-liquid extraction (PLE), bioactive assays and comprehensive HRMS-based phytochemical characterization to obtain bioactive-rich fractions with high antioxidant capacity and antiproliferative activity against human colon cancer cells. Thus, a two steps PLE procedure was proposed to recover first the non-polar fraction (fatty acids and lipids) and second the polar fraction (polyphenols). Efficient selection of the most suitable solvent for the second PLE step (ethanol/ethyl acetate mixture) was based on the Hansen solubility parameters (HSP) approach. A comprehensive GC- and LC-Q-TOFMS/MS profiling analysis allowed the complete characterization of the lipidic and phenolic fractions obtained under optimal condition (100% EtOH at 150 °C), demonstrating the abundance of oleic and stearic acids, as well as bioactive xanthones, phenolic acids, flavonoids, gallate derivatives and gallotannins. The obtained MSKextract exhibited higher antiproliferative activity against human colon adenocarcinoma cell line HT-29 compared to traditional extraction procedures described in literature for MSK utilization (e.g. Soxhlet), demonstrating the great potential of the proposed valorization strategy as a valuable opportunity for mango processing industry to deliver a value-added product to the market with health promoting properties.